Polymerisation of Acrylamide initiated by Ce(IV)-Iminodiacetic acid Redox system - Nalla Mohamed, K.E.N. (Asian Journal of Chemistry, 2010)
Polymerisation of acrylamide initiated by ceric ammonium sulphate Ce(IV) in combination with iminodiacetic acid (IDA) has been investigated in aqueous solution. Polymerisation behaviour as a function of the concentration of Ce(IV), IDA and acrylamide as well as temperature have been studied. The polymerisation is initiated by the radical produced from the decomposition of the complex formed between Ce(IV) and IDA. The rate of polymerisation is found to be first order with respect to the concentration of monomer and complex. The complex formation constant (K) and disproportionation constant (kd) of Ce(IV)-IDA chelated complex are evaluated and they are 9.043 x 102 and 2.096 x 10–3 respectively. The effect of excess of Ce(IV), mineral acid and complex (initiator) concentrations were studied. The Rp value gradually increases to a maximum and then decreases with increase of complex concentration. The kinetic parameters involved were determined.